A Comparative Docking Strategy to Identify Polyphenolic Derivatives as Promising Antineoplastic Binders of G‐quadruplex DNA c‐myc and bcl‐2 Sequences. Issue 8 (24th June 2016) - Costa, Giosuè; Rocca, Roberta; Moraca, Federica; Talarico, Carmine; Romeo, Isabella; Ortuso, Francesco; Alcaro, Stefano; Artese, Anna
Abstract: Polyphenols are compounds ubiquitously expressed in plants and used for their multiple healthy effects in humans as anti‐inflammatory, antimicrobial, antiviral, anticancer and immunomodulatory agents. Due to their ability to modulate the activity of multiple targets involved in carcinogenesis, polyphenols can be employed to inhibit the growth of cancer cells. Several studies reported their high affinity to different G‐quadruplex DNA structures, including the oncogene promoters c‐myc and bcl‐2 . In this work we applied a structure‐based virtual screening approach in order to screen a database of polyphenolic derivatives and human metabolites against both c‐myc and bcl‐2 DNA G‐quadruplex structures. A Delphinidine derivative was identified as the best " dual " candidate and, after molecular dynamics simulations, resulted able to well stabilize both receptors. Abstract :